Women’s expectations and experiences regarding e-health treatment: A systematic review - Verhoeks, Carmen (Health Informatics J, 2017)
There is a gap in knowledge of women’s perceptions of e-health treatment. This review aims to investigate women’s expectations and experiences regarding e-health. A search was conducted in MEDLINE, EMBASE, CINAHL and PsycInfo in March 2016. We included articles published between 2000 and March 2016, reporting on e-health interventions. The initial search yielded 2987 articles. Eventually, 16 articles reporting on 16 studies were included. Barriers to e-health treatment were lower for women than barriers to face-to-face treatment, such as feelings of shame and time constraints. Women were able to develop an online therapeutic relationship. As reduced feelings of obligation and lack of motivation were women’s greatest challenges in completing e-health treatment, they expressed a wish for more support during e-health treatment, preferably blended care. e-Health lowers the threshold for women to seek healthcare. Combining e-health interventions with face-to-face sessions may enhance women’s motivation to complete treatment.